Efeito da proteína morfogenética óssea 15 (bmp15) no cultivo in situ de tecido ovariano de catetos (pecari tajacu linnaeus, 1958) - Gomes, Henrique Albano Nogueira (2019)
Collared peccaries are wild animals that have a great ecological importance and economic potential. Thus, in order to increase reproductive potential this species, biotechniques such as in vitro culture of preantral follicles have been studied. It is known preantral folliculogenesis is regulated by autocrine and paracrine factors in an orchestrated mechanism that defines the course of development or death. Among these factors is bone morphogenetic protein 15 (BMP15), which acts on activation, survival and follicular development in different species. Nevertheless, the roles of BMP15 in the regulation of primordial follicle development in collared peccaries remains unknown. The aims of present study were to investigate the effects of BMP15 on in vitro culture of collared peccaries preantral follicles using histological studies. To this end, fragments of collared peccaries (Pecari tajacu) ovarian cortex were cultured for 1 or 6 days, at 38.5 °C in an atmosphere containing 5% CO2, in TCM199+ (control medium) supplemented with different concentrations of recombinant human BMP15 (rhBMP15, R&D Systems, Minneapolis, MN, USA) (1, 25 and 50 ng/mL). The fresh control and cultured fragments were fixed, processed for classical histology (hematoxylin/eosin and AgNOR), and the ovarian follicles were evaluated for morphology, classified as normal or degenerate, and classified as primordial or developing (primary and secondary). The latter parameter was used for study of follicular activation, taking into account the ratio between percentage of primordial and developing follicles throughout the culture. In addition, follicles and oocytes were measured before and after culture to record follicular and oocyte growth. The cell proliferation of ovarian follicles during experiment was evaluated by counting the nucleolar organizing regions (NORs) by the AgNOR technique. The fresh control showed high rates of follicles with normal morphology (92.68% ± 1.09) and, after culturing, addition of BMP15 (25 ng/mL) to medium resulted in a higher percentage of normal follicles (79.67 ± 0.69) compared to the other treatments (P<0.05), except for 1 ng/mL BMP15 (74.00% ± 1.90) (P>0.05). In addition, higher concentrations of BMP15 (25 ng/ml and 50 ng/ml) stimulated the activation of primordial follicles in relation to cultured control (P<0.05). However, this substance did not demonstrate effects on oocyte and follicular growth. All concentrations of BMP15 used increased the number of NORs after 1 day of cultivation relative to fresh and cultivated control (P<0.05), and, after 6 days, number of NORs in fragments cultured in all treatments was higher than that observed in fresh control (P <0.05). In conclusion, the addition of 25 ng/ml of BMP15 to culture medium of preantral follicles of peccaries maintains a high number of morphologically healthy follicles and stimulates activation of primordial follicles after 6 days of culture